A-GATECH: GREEN INNOVATION OF IOT-PHOTOVOLTAIC MICROALGAE FROM E-WASTE-FOR- CAPTURE CO₂ DECARBONIZATION AND BIODIESEL PRODUCTION SUPPORTING LOW-CARBON ENERGY BUSINESS - Bayu Aji (Institut Teknologi Sepuluh Nopember, 2026)
Global carbon dioxide (CO₂) emissions reached 36.8 billion tons in 2023, with industry and transportation contributing more than 65%. In Indonesia, emissions have increased by an average of 3.5% per year, highlighting the urgent need for effective mitigation solutions that also generate economic value. Therefore, this study focuses on the development of A-Gatech (Algae-based Green Technology), an innovation utilizing a tubular photobioreactor made from electronic glass waste (e-waste), powered by solar energy, and equipped with an IoT-based control system. The aim of this research is to design, test, and analyze the performance of A-Gatech in capturing CO₂ while simultaneously producing biodiesel as an economically valuable product. The research steps include a literature review, prototype design, laboratory validation, limited trials, field testing, and technical as well as economic feasibility analysis using the Technology Readiness Level (TRL) approach. Simulation and statistical results show that A-Gatech can capture up to 653 tons of CO₂ per hectare per year with an efficiency of 1.8 kg/m²/day, produce up to 198,000 liters of biodiesel per hectare per year valued at approximately IDR 1.98 billion, and reduce electronic waste by around 10 tons annually. Business feasibility analysis indicates that the production break-even point (BEP) can be achieved at 21 units per month, with a profit margin of around 65%. In conclusion, A-Gatech is feasible for implementation as it not only contributes to climate change mitigation but also supports the circular economy and creates green jobs. This innovation is aligned with the Sustainable Development Goals, particularly Goal 7 (Affordable and Clean Energy), Goal 11 (Sustainable Cities and Communities), Goal 12 (Responsible Consumption and Production), and Goal 13 (Climate Action).